2011 IEEE Global Engineering Education Conference (EDUCON) 2011
DOI: 10.1109/educon.2011.5773141
|View full text |Cite
|
Sign up to set email alerts
|

An assistive computerized system for children with moderate intellectual and learning disabilities

Abstract: We aim in this project to develop a system for children with intellectual and learning disabilities that supports collaboration, data exploration, communication and creativity. The system offers specific tutorials on basic concepts. It can enhance the communications and learning capabilities of the children. The tutorial contents contains multimedia elements that help the children understand effectively the topics. An assessment component is being developed to evaluate the children understanding. Parents can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Mobile applications [14], [15], [16], [17], [18], [19], [20], [21], [22], [23] Augmented reality [24], [25], [26], [27], [28], [29] Digital tools [30], [31], [32], [33] Web applications [34], [35], [36], [37], [38], [39], [40], [41], [42] Desktop applications [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55],…”
Section: Category Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile applications [14], [15], [16], [17], [18], [19], [20], [21], [22], [23] Augmented reality [24], [25], [26], [27], [28], [29] Digital tools [30], [31], [32], [33] Web applications [34], [35], [36], [37], [38], [39], [40], [41], [42] Desktop applications [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55],…”
Section: Category Articlesmentioning
confidence: 99%
“…[30], [31], [32], [33] These articles argue that the use of educational software aims to improve teaching processes and blended learning in different types of schools.…”
Section: Themes and Functionality Referencesmentioning
confidence: 99%
“…Consequently, it is essential to seek out an effective intervention that can help and improve the lives of the autistic persons (Lindgren & Doobay, 2011). Alja'am and Jaoua (2011) reported that autistic children who are experiencing learning difficulties can be assisted by providing them with suitable assistance and various learning materials, with some encouragement. According to Corsello (2005), each intervention program is founded on a distinctive approach and adopts unique intervention strategies, which focus on support and learning environment for autistic persons apart from supporting these persons replace the challenging behaviour with more proper behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitous learning technology can support dyslexic, visually impaired and foreign language learners [4][5][6] and immersive technologies such as high definition Augmented Reality (AR) can provide students with an inclusive and engaging experience [7]. The same is also true for the business community, giving architects, engineers, artists and clinicians a futuristic method to share vision and creativity in conference/meeting room environments.…”
Section: Introductionmentioning
confidence: 99%